2017
DOI: 10.1093/pch/pxx017
|View full text |Cite
|
Sign up to set email alerts
|

Cannabis and Canada’s children and youth

Abstract: Cannabis is the most common illicit drug used worldwide and it is used frequently by Canadian teenagers. Cannabis use during adolescence can cause functional and structural changes to the developing brain, leading to damage. Marijuana use in this age group is strongly linked to: cannabis dependence and other substance use disorders; the initiation and maintenance of tobacco smoking; an increased presence of mental illness, including depression, anxiety and psychosis; impaired neurological development and cogni… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
41
0
3

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 56 publications
(44 citation statements)
references
References 54 publications
0
41
0
3
Order By: Relevance
“…Despite the increased cannabis use in children and adolescents, 7 the main focus of research has been on the psychiatric outcomes and neurocognitive deficits resulting from its use, while the impact on physical health has received less attention. 10 Pediatricians and other health care providers require high-quality information to council their young patients regarding the potential physical health effects of cannabis, as this may influence the decision of children and youth to use cannabis. In addition, this information may also clarify the need for policy makers to support the development of screening and treatment strategies for those who decide to use cannabis, if potential negative health impacts are identified to reduce potential harms on physical health and development.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Despite the increased cannabis use in children and adolescents, 7 the main focus of research has been on the psychiatric outcomes and neurocognitive deficits resulting from its use, while the impact on physical health has received less attention. 10 Pediatricians and other health care providers require high-quality information to council their young patients regarding the potential physical health effects of cannabis, as this may influence the decision of children and youth to use cannabis. In addition, this information may also clarify the need for policy makers to support the development of screening and treatment strategies for those who decide to use cannabis, if potential negative health impacts are identified to reduce potential harms on physical health and development.…”
Section: Discussionmentioning
confidence: 99%
“…While studies have focused on the mental and neurocognitive effects of cannabis use, 10 13 there is currently limited evidence regarding the effects of its use on the physical health of children, including endocrine and metabolic health.…”
Section: Introductionmentioning
confidence: 99%
“…181,182 A review of the literature by the Canadian Paediatric Society concluded that cannabis use during adolescence can cause changes to the developing brain, and has been linked to substance use disorders, tobacco smoking, increased rates of psychiatric illnesses, cognitive decline, and diminished school performance and lifetime achievement. 184,185 They recommended that sales of all cannabis products to children and adolescents be prohibited in order to protect these individuals from the potential harms associated with cannabis use. 184,185 Based on the lack of evidence for efficacy in the treatment of CD, and the potential harms associated with long-term use, the consensus group made a strong recommendation against the use of cannabis products in pediatric patients with CD.…”
Section: Alternative Therapiesmentioning
confidence: 99%
“…184,185 They recommended that sales of all cannabis products to children and adolescents be prohibited in order to protect these individuals from the potential harms associated with cannabis use. 184,185 Based on the lack of evidence for efficacy in the treatment of CD, and the potential harms associated with long-term use, the consensus group made a strong recommendation against the use of cannabis products in pediatric patients with CD.…”
Section: Alternative Therapiesmentioning
confidence: 99%
“…Further, there is increasing empirical evidence suggesting that the consumption of cannabis may disrupt the neurodevelopmental processes in young adults. The disruption in the neurodevelopmental process has been found to contribute to increased cannabis-related dependence, mental health disorders (i.e., psychosis, anxiety, and depression), short-and long-term cognitive impairment (affecting self-control, learning, memory, and attention span), engagement in risky behavior (i.e., driving while under the influence of cannabis), dropping out of school, and not pursuing a higher level of education [20][21][22][23][24].…”
Section: Introductionmentioning
confidence: 99%